1989
DOI: 10.1038/337525a0
|View full text |Cite
|
Sign up to set email alerts
|

Designing CD4 immunoadhesins for AIDS therapy

Abstract: A newly-constructed antibody-like molecule containing the gp120-binding domain of the receptor for human immunodeficiency virus blocks HIV-1 infection of T cells and monocytes. Its long plasma half-life, other antibody-like properties, and potential to block all HIV isolates, make it a good candidate for therapeutic use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
240
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 596 publications
(251 citation statements)
references
References 49 publications
5
240
0
Order By: Relevance
“…This protein was expected to be more efficient therapeutically than tsCR1 itself, since the tsCR1-Ig molecule is likely to have an increased half-life compared with tsCR1, due to the presence of the IgG Fc region (68,69). In addition, the IgG Fc region in the tsCR1-Ig molecules enables it to form homodimers.…”
Section: Resultsmentioning
confidence: 99%
“…This protein was expected to be more efficient therapeutically than tsCR1 itself, since the tsCR1-Ig molecule is likely to have an increased half-life compared with tsCR1, due to the presence of the IgG Fc region (68,69). In addition, the IgG Fc region in the tsCR1-Ig molecules enables it to form homodimers.…”
Section: Resultsmentioning
confidence: 99%
“…The TNF inhibitor that we have produced and characterized finds precedent in the work of Capon et al (16) and Traunecker et al (17), who designed secreted chimeric molecules in which the binding moiety of a CD4 molecule was adjoined to an IgG heavy chain. This molecule circulated for a prolonged period of time in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…33 More importantly, previous studies have shown that IFN␥R/Fc fusion proteins have a much longer half-life in body fluids than truncated IFN␥R, 23 possibly because the larger size of immunoadhesins prevents rapid clearance in the kidney. 34 Also, dimeric IFN␥R/Fc fusion proteins can usually bind IFN␥ with greater avidity than single chain receptors, presumably because this cytokine is a homodimer. 33 For insertion into the vector, we chose heavy chain elements (part of CH1, hinge, CH2 and CH3) of the murine IgG1 isotype, instead of other isotypes, because IgG1 has a long half-life in serum and does not activate complement.…”
Section: Discussionmentioning
confidence: 99%